2009
DOI: 10.1182/blood-2008-05-158584
|View full text |Cite
|
Sign up to set email alerts
|

Integrin αvβ3 on human endothelial cells binds von Willebrand factor strings under fluid shear stress

Abstract: Acutely secreted von Willebrand factor (VWF) multimers adhere to endothelial cells, support platelet adhesion, and may induce microvascular thrombosis. Immunofluorescence microscopy of live human umbilical vein endothelial cells showed that VWF multimers rapidly formed strings several hundred micrometers long on the cell surface after stimulation with histamine. Unexpectedly, only a subset of VWF strings supported platelet binding, which depended on platelet glycoprotein Ib. Electron microscopy showed that VWF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
142
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(158 citation statements)
references
References 45 publications
13
142
3
Order By: Relevance
“…Previous findings from our laboratory (see supplemental Figure 4C in reference 29) and others 31,33,34 have shown that unstimulated cells only rarely form VWF strings under flow. This is consistent with our proposed role for basal VWF, again suggesting that, although being of similar high multimeric states (except for the dimer band), basal and regulated VWF play different functional roles.…”
Section: Discussionsupporting
confidence: 49%
“…Previous findings from our laboratory (see supplemental Figure 4C in reference 29) and others 31,33,34 have shown that unstimulated cells only rarely form VWF strings under flow. This is consistent with our proposed role for basal VWF, again suggesting that, although being of similar high multimeric states (except for the dimer band), basal and regulated VWF play different functional roles.…”
Section: Discussionsupporting
confidence: 49%
“…In healthy scenarios, the endothelium provides a nonadhesive and antithrombotic interface for the transport of blood through the vessel whereas during inflammation, the endothelium promotes the formation of the thrombi via local expression and secretion of adhesive proteins (33). The interaction of blood with endothelium has been studied extensively in vitro in planar formats that lack appropriate vessel geometries or a 3D matrix (34,35). We examined the interaction of whole blood and the endothelium in μVNs in a quiescent state (after 7 to 14 d in our standard microfluidic culture; see Methods and SI Methods) and a stimulated state induced by brief exposure to phorbol-12-myristate-13-acetate (PMA).…”
Section: Resultsmentioning
confidence: 99%
“…S7 D and E). Such structures have not been reported in planar cultures in which the flow is uniaxial and parallel to the endothelium (35), or in mouse models, where details of the progression of thrombosis have been difficult to resolve (40).…”
Section: Resultsmentioning
confidence: 99%
“…6 Self-association also allows VWF to form strands long enough to reach above the endothelial boundary layer under flow to bind platelets, which may explain the findings of a study showing that platelets bound only a subset of endothelial VWF strings identified with a VWF antibody. 14 On the basis of our observation that highly purified VWF was lost from solution by first binding to the wall of the container and then by There is an Inside Blood Commentary on this article in this issue.…”
Section: Introductionmentioning
confidence: 99%